Effect Of Diabetes Mellitus On Thyroid Gland Physiology And Hormone - Abd Ali, Rusul Arif; AL-mayali, Zahraa Kareem; Hamza Al-Kraity, Asst.Prof.Dr. Wijdan Rajh (Medical Science Journal for Advance Research, 2023)
Backgraund: Thyroid gland is considered biggest ductless gland in human, consist of many follicular cells called colloid that responsible for production of glycoprotein thyroglobulin. Itis secrete T3,T4, TSH and calcitonin hormone that increase the metabolic rate of the body, growth and differentiation. thyroid hormone acting a role in regulatory metabolism of glucose and pancreatic role, but diabetes mellitus changed thyroid function. Such as, “TSH to thyrotropin-releasing hormone response” it is reduced in diabetes, that lead to accompanying reduced T3 level and hypothyroidism, together hypothyroidism and hyperthyroidism lead to insulin resistance. In this study show significant decrease in Hb , RBC,WBC and Hba1c level in male and female patient as compare with control, also show significant increase in Glucose level in both male and female patients as compare with control, and significantly decrease in TSH T3 and T4 level in female and male patients as compare with control. Thyroid hormones cause immediate effect on the blood parameter by inducing the precursors of the erythrocyte and indirectly by stimulating erythropoietin manufacture, also diabetes effect on thyroid function by changing the thyroid-stimulating hormone (TSH) level and weakening the alteration of thyroxine (T4) to triiodothyronine (T3) in the peripheral tissues.